Hadith in Social Media: Study of Ustaz Adi Hidayat's Hadith Submission on the "Adi Hidayat Official" Youtube Channel - Andi Fatihul Faiz Aripai; Nur Laili Nabilah Nazahah Najiyah (Spiritus: Religious Studies and Education Journal, 2023)
In the digital era, the most pronounced change in the field of hadith studies is the ease of finding hadith studies of the Prophet Muhammad. on social media. The spread of hadith studies on social media carried out by these ustaz helped make it easier for the common Muslim community to understand a hadith related to certain themes. One of the figures who plays an active role in studying hadith on social media is Ustaz Adi Hidayat. Therefore, this paper aims to see how the delivery and understanding of the hadith given by Ustaz Adi Hidayat on social media is a form of transformation of the delivery of hadith from classical to digital. This paper uses a qualitative research method based on the Youtube video kanal "Adi Hidayat Official" as primary data. While the secondary data is some literature in the form of books, journals, and research related to the same theme. The analysis of research data was carried out by condensation, display, and data conclusion/verification that took place simultaneously. As a result, Ustaz Adi Hidayat is a figure who can be said to be qualified in the field of hadith. On the Youtube kanal "Adi Hidayat Official", he examines hadith based on certain themes both textually, intertextually and contextually, and also presents several different views of scholars to provide a more comprehensive and complex understanding. This can be seen in the uploaded content entitled "Four Features of Ramadan - Ustaz Adi Hidayat" and the playlist "Ramadan 1444 H Program: Kitabus Shaum 2023".